Ein In-vitro-Mausmodell für die Palatogenese und die Entstehung von Gaumenspalten - Von den Hoff, Johannes W; Fuentes, Laury A Roa; Bloemen, Marjon; Kuijpers-Jagtman, Anne Marie (Informationen aus Orthodontie & Kieferorthopädie, 2017)
The mouse is an excellent model to study palatogenesis since, like humans, it is a mammal, it can easily be bred and a wide array of molecular tools are available. Moreover, the isolated embryonic mouse palate can be cultured in vitro, which allows us to study the actual fusion process in detail.Just prior to the actual fusion at E13, the maxilla with the 2 palatal shelves can be dissected from the embryo head. The maxilla is cultured on a filter paper on top of a stainless-steel grid at the interface of the culture medium and air. After 24 h in culture, the palatal shelves are in contact and the MES is clearly visible. At 48 h, the MES has nearly completely disintegrated with small remnants at the nasal and oral side of the palate. Finally, at 72 h, the palatal shelves are completely fused and osteoid tissue is beginning to form in the lateral areas.The exact downstream molecular mechanisms that lead to clefting are far from being unraveled. The model for palate fusion presented here offers the possibility to analyze the molecular and cellular mechanisms that lead to clefting as a result of specific genetic and environmental factors. This will pave the way to pharmacological intervention for the prevention of cleft lip and/or palate in susceptible individuals.
Keywords: Gaumenspalte; Embryologie; Maus; In-vitro-Verfahren